DFT Calculation for Newly Synthesized 2-Chloro-1-(3-methyl-3-mesityl-cyclobutyl)– ethanone - Koparir, Pelin; Omar, Rebaz Anwar (AMG Transcend Association, 2023)
The synthesis of cyclobutane rings, particularly stereospecifically, poses significant challenges in synthetic chemistry due to the highly strained ring topologies. The cyclobutane-containing natural products are appealing targets for total synthesis due to their new chemical structures and exceptional biological activity. In this study, we have presented the synthesis and structure analysis of 2-chloro-1-(3-methyl-3-mesityl-cyclobutyl)–ethanone. The molecular elucidation was conducted by Fourier transform infrared (IR) and Nuclear magnetic spectroscopy (NMR). The I recording in 4000-500cm-1 was done in the potassium bromide solid phase, while the NMR for both Hydrogen and Carbon was done in the Dimethyl sulfoxide-6. Density functional theory (DFT) was used to stimulate and confirm the structure and molecular characterization. Using DFT/cc-pVDZ method to study various conformers of the compound and their minimum energies by the scanning potential energy surface. In addition, the molecular electrostatic potential map (MEP) and charge spreading have been plotted for the molecule to account for the chemical reactivity and site selectivity. Furthermore, the thermodynamic properties of the molecule have been studied. A good correlation was found between experimental and stimulation studies for Fourier transform infrared and Nuclear magnetic spectroscopy results. In the stimulation data, the conformer's energy differences were very small. © 2022 by the authors.
Keywords: cyclobutane; density functional theory; molecular electrostatic potential map; molecular reactivity; thermodynamic properties